Landscape habitat occupancy and distribution of the Wild Ground Pangolin (Smutsia temminckii) in Zimbabwe's Protected Areas (PAs) - Innocent Mahakata; Prudence Gonhi; Spencer Matindike; Yvonne Masumba; Christopher Hungwe (Global Journal of Ecology - Peertechz Publications, 2021)
The Smutsia temminckii is the only species of pangolin known to exist in Zimbabwe and is considered vulnerable under the IUCN Red List of threatened species. Distribution of wild S. temminckii in protected areas (PAs) and associated environmental variables are not well defined in Zimbabwe. The study sort to relate key environmental variables (Altitude, rainfall, temperature and vegetation type) to habitat occupancy and distribution of S. temminckii. Data was collected from forty-eight stations based on S.temminckii sightings historical records spanning ten years (2011-2021) done by field rangers, tourists and scientific services research personnel. A review of available literature was done from online sources and station records. A distribution map based on S. temminckii sightings across various PAs in Zimbabwe was developed for this study. Results of this study reveal that S. temminckii occupy PAs in South East low-veld areas, Northwestern Zimbabwe, Mid Zambezi Valley and Nyanga NP. No historical data on S. temminckii sighting in central PAs located in ecological regions IIa, IIb and III of Zimbabwe. Climatic conditions associated with S. temminckii distribution, except for Nyanga NP, are average temperatures above 220C and rainfall between 400mm to 900mm per annum. Landscapes ideal for S. temminckii habitat occupancy have an altitude between 262m-2000m above sea level. Associated vegetation types for habitat occupancy of S. temminckii are the Zambezian and mopane woodlands as well as montane forest grasslands mosaic of Nyanga NP. Future studies should focus on establishing distribution of S. temminckii outside PA, population status and density to inform conservation of this rare and unique species around Zimbabwe.